Factors Affecting Investment Decisions On Millennials And Gen Z - Annabella Claudia Kurniadi; Christian Herdinata (Jurnal Manajemen, 2024)
Since 2019, capital market investors have surged, primarily those under 40 years old, called millennials and Gen Z. However, the financial literacy of Indonesians is low, with victims of fictitious investment cases increasing yearly. This study aims to determine the effect of Financial Literacy (FL) and Investment Experience (IE) on Investment Decisions (ID) with Risk Tolerance (RT) as a mediating variable. The method used is Partial Least Square and involves 185 stock investors aged 18 to 40 years domiciled in Java and Bali, using a purposive sampling technique and the Hair formula. This study found that FL and IE have a significant and positive effect on ID, FL and IE have a significant and positive effect on RT, RT has a significant effect and positive on ID, FL and IE have a significant and positive effect on ID through RT.